A Survey of Urinary and Faecal Incontinence Among Children with Cerebral Palsy in Selected Tertiary Hospitals in South-West Nigeria - A., Zaki Desmond; A., Karaga Mahmud; Raphael, Christopher; A., Saleh Baba; G., John-Chu Cindy; O., Adeleke Joana; T., Akintunde Ireoluwa (African Journal of Medicine, Surgery and Public Health Research, 2025)
Background: Previous studies have investigated the prevalence of Urinary Incontinence (UI) in children with cerebral palsy (CP), and yet a very few others have looked at Faecal incontinence (FI) in this population. However, there is a notable dearth of research on the association between UI and FI amongst this population particularly in the South-west Nigeria. Aim: To examine the prevalence of UI and FI in children with CP, as well as the association between UI and FI among this population in South-west Nigeria. Methods: Consecutive sampling technique was used to enlist 77 participants attending outpatient physiotherapy clinics in tertiary hospitals in Oyo, Osun, Ondo, Lagos and Ekiti states in south-western Nigeria. ICIQ-CLUTS questionnaire, Wexner/Cleaveland Clinic Florida Incontinence Score, Gross Motor Function Classification System (GMFCS) were administered to the participants through their primary caregivers. Descriptive statistics was used to summarize participants’ socio-demographic data. Inferential statistics of chi-square was used to determine the association between selected socio-demographic characteristics and each of UI, FI and GMFCS among participants. Spearman correlation was used to test the relationship between selected socio-demographic characteristics and each of UI, FI and GMFCS among participants. Data was analyzed using SPSS version 21.0 at 0.05 alpha level. Results: Among the participants, 51.9% were females and 48.1% were males, the mean age was 2.08 ± 0.82. Prevalence of UI amongst children with CP showed majority (79.2%) experiencing moderate symptoms, (19.5%) severe symptoms and (1.3%) experienced extremely severe symptoms. Prevalence of FI showed moderate symptoms in (62.3%), mild symptoms in (31.2%) and severe symptoms in (5.2%). However, no significant relationship or association was found among socio-demographic variables and (UI, FI, GMFCS). Conclusion: This study shows a 100% prevalence of UI and 98.7% of FI among children with Cerebral Palsy, underscoring the urgent need for comprehensive care and management strategies. The associated physical, psychological, and social implications for both the child and family cannot be overemphasized.